Implementasi Undang-Undang Wakaf No. 41 Tahun 2004 dan Peraturan Pemerintah No. 42 Tahun 2006 terhadap Pengelolaan Harta Wakaf - Paridatul Amriah (Center for Religious Studies and Social Empowerment Foundation, 2023)
This article aims to find out how management, problems and how the implementation of the Waqf Law No. 41 of 2004 and Government Regulation no. 42 of 2006 on the Management of Waqf Assets and solutions to the management of waqf assets in Batin VIII District, Sarolangun Regency, Jambi Province. This type of research is field research, the research approach is a qualitative approach using descriptive methods, the types of data used are primary and secondary data, the source of data is from sources. While the data collection methods are observation, interviews, and documentation. Based on the results of the study, it was concluded that the Implementation of Waqf Law No. 41 of 2004 and Government Regulation no. 42 of 2006 regarding the Management of Waqf Assets in the District of Bathin VIII, Sarolangun Regency, Jambi Province has not been realized properly and optimally. With the problems of waqf that occur, namely Nazhir who does not have professional certification, waqf land that does not have waqf certification and pledge deed, lack of socialization of waqf to the community so that there is a lack of understanding of waqf in society, a lack of sense of responsibility for nazhir, there are land dispute problems that occur , requires serious handling, data on waqf assets is minimal. The solution is for nazhir to socialize, at least give lectures at religious activities to the public regarding waqf, increase waqf data collection, utilization and management of waqf assets, increase nazhir's accountability by conducting coaching. Artikel ini bertujuan untuk mengetahui bagaimana pengelolaan, problematika serta bagaimana Implementasi Undang-udang Wakaf No. 41 Tahun 2004 dan Peraturan Pemerintah No. 42 Tahun 2006 Terhadap Pengelolaan Harta Wakaf dan solusi terhadap pengelolaan harta wakaf di Kecamatan Batin VIII, Kabupaten Sarolangun, Provinsi Jambi. Jenis penelitian adalah penelitian lapangan, Pendekatan penelitian adalah pendekatan kualitatif dengan mengunakan metode deskriftif, jenis data yang digunakan adalah data primer dan skunder, sumber data dari nasumber. Sedang metode pegumpulan data adalah observasi, wawancara, dan dokumentasi. Berdasarkan hasil penelitian, diperoleh kesimpulan bahwa Implementasian Undang-undang Wakaf No. 41 Tahun 2004 dan Peraturan Pemerintah No. 42 Tahun 2006 Terhadap Pengelolaan Harta Wakaf di Kecamatan Bathin VIII, Kabupaten Sarolangun, Provinsi Jambi masih belum terealisasikan secara baik dan optimal. Dengan adanya problematika wakaf yang terjadi yaitu Nazhir yang tidak memiliki sertifikasi profesi, tanah wakaf yang tidak memiliki setifikasi dan akta ikrar wakaf, kurangnya pensosialiasian wakaf kepada masyarakat sehingga minimnya pemahaman wakaf di masyarakat, rasa tanggung jawab nazhir yang kurang, adanya permasalahan sangketa tanah yang terjadi, memerlukan penanganan serius, data-data harta wakaf yang minim. Solusinya adalah nazhir melakukan pensosialisasian, setidaknya melakukan ceramah di kegiatan keagamaan kepada masyarakat mengenai perwakafan, meningkatkan pengumpulan data wakaf, pemanfaatan dan pengelolaan harta wakaf, meningkat pertanggungjawaban nazhir dengan melakukan pembinaan.